2018
DOI: 10.29333/ejmste/90991
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Students’ ICT Readiness for a Blended Teaching and Learning Environment

Abstract: Information Communications Technology (ICT) plays an important role in enhancing Chinese students' learning efficiency and preparation for successful participation in a Western learning and teaching community. In the past, Chinese students' ICT preparedness for Western higher-education has not been emphasized in Chinese domestic K-12. Consequently, this lack of skills might be the cause tension between students and university academics in a blended learning and teaching environment. This pilot study used the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Although LMS and the nature of instructional activity are entirely different from the use of ICT for entertainment or other productive purposes [15], [39], but this initial knowledge is quite capable of building beliefs within lecturers and students. This view is in line with previous research findings, which suggest that the readiness of educational organizations in integrating technology in learning activities depends on teacher readiness and teacher readiness depends on belief and perceived skills [11], [40].…”
Section: Respondsupporting
confidence: 92%
See 2 more Smart Citations
“…Although LMS and the nature of instructional activity are entirely different from the use of ICT for entertainment or other productive purposes [15], [39], but this initial knowledge is quite capable of building beliefs within lecturers and students. This view is in line with previous research findings, which suggest that the readiness of educational organizations in integrating technology in learning activities depends on teacher readiness and teacher readiness depends on belief and perceived skills [11], [40].…”
Section: Respondsupporting
confidence: 92%
“…Cheon et al [5] revealed that lecturers and students who have the readiness to integrate IT would benefit from the use of a learning management system (LMS) and then will produce an attitude of acceptance and adoption to support the learning process. Besides, technological readiness will also improve the quality of online learning and teaching to be meaningful [11]. The challenge is, the readiness of technology referred to in academic activities is not just an understanding of technology, but how to utilize the technology to support learning and teaching activities [15].…”
Section: Unimed Itself Has Held Training and Workhops On The Development Of Syllabus And Semester Instructionalmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, technologies affect most aspects of our daily work as they have produced changes in every sphere of society [16], [17], including education [18], [19]. Moreover, they help EFL learners enhance their language abilities [20], [21]. "There are many benefits to using ICTs (information and communication technologies) as an educational tool" [22, p. 176].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon also disrupts the way students study. Previous learning activities must be done at certain times, specific places, and with thick textbooks that have the potential to change to be very flexible with the availability of various information in hand (see: Lu and Price, 2018). Classrooms are now available anywhere, anytime, with virtually available textbooks.…”
Section: Introductionmentioning
confidence: 99%